The Relationship Of Anti-Inflammation Non Steroid Use Patterns With Side Effects In Patients Post Appendectomy At Jemursari Islamic Hospital - Lailia, Shafira Nur; Handayani, Handayani; Bhayusakti, Aditya; Adriansyah, Agus Aan (UNUSA Press, 2023)
Background: Appendicitis is a condition where there is acute inflammation of the vermiform appendix which causes patients to undergo surgery frequently. NSAIDs are given to patients after appendectomy surgery to relieve pain. Inappropriate pattern of NSAID use can cause drug side effects. Objective: This study aims to analyze the relationship between the pattern of use of non steroidal anti-inflammatory analgesics and drug side effects in post-appendectomy patients at Jemursari Hospital Surabaya in 2019-2020. Methods: This type of research is descriptive analytic with a cross sectional design. This study used 62 samples medical record of post-appendectomy patients in 2019-2020 who were given NSAID therapy. Chi-Square Test and Fisher's Exact Test (p<0.05) was used to analyze the relationship between NSAID use patterns and side effects. Results: There was a relationship between the type of drug Mafenamic Acid 500mg with nausea, Ketorolac 30mg with hypotension, Ketorolac 90mg with dizziness, and Santagesic 500mg with dyspepsia (p<0.05). Administration of therapy with less dose was associated with hypotension (p<0.05). The duration of therapy for 4 days was associated with nausea, vomiting and duration of therapy for 5 days was associated with constipation and dyspepsia. Conclusion: The use of drugs (type of drug, accuracy of dose and duration of therapy) of NSAIDs in post-appendectomy patients is associated with drug side effects.